Veridical Flashbacks and Dreams of a Pre-Christian Life in Norway, Following a Near-Death Experience in Adulthood - Matlock, James G. (Journal of Scientific Exploration, 2025)
Following a near-death experience (NDE) at 28, a woman began to have visions of an apparent past life in the region of southern Norway where she lives presently but set toward the end of the pre-Christian era, in the 900s CE. Altogether, she had five flashbacks triggered by places or views, six memory dreams that may also have been triggered, and two related experiences, all pertaining to the life of a vǫlva, a Viking sorceress or witch. One of the dreams, depicting a stone circle ritual, repeated nightly for six weeks. Given the great time depth involved, it is impossible to identify the apparent memories with any specific individual, but their general tenor conforms with what is known about Viking Age practices from archeological investigations and readings of Old Norse epic poems. This unusual reincarnation case demonstrates the importance of cuing in past-life memory retrieval and suggests that NDEs may play a role in this as well.